Assessment of genetic diversity in mungbean (Vigna radiata L. Wilczek) landraces under tropical environment of Andaman & Nicobar Islands - Singh, Awnindra K.; Gautam, R.K.; Kumar, Naresh; Singh, P.K.; Kumar, Krishna; Roy, S. Dam (The Indian Journal of Genetics and Plant Breeding, 2016)
A study was conducted to determine the genotypic and phenotypic variance and genetic diversity for yield and its attributing traits in 56 germplasms of mungbean. Significant variation among the landraces and genotypes was recorded. Using cluster analysis by UPGMA method, all the genotypes were grouped into 3 major and one minor groups. Cluster I consisted 10 genotypes, cluster II 20, Cluster III 24 and cluster IV 2 genotypes. The pattern of distribution of genotypes from different locations into four clusters was random, demonstrating that geographical isolation may not be the only factor causing genetic diversity. More emphasis should be given on cluster III for selecting genotypes as parents for crossing with the genotypes of cluster I. Principal component analysis explained nearly 74% of total variation among genotypes. By plot of first two components score for genotypes confirmed the results of cluster analysis.